The Paris Climate Agreement in online media - Mossiagina, Maria (2016)
The thesis examines media discussions after the adoption of the Paris Climate Agreement on 12 December 2015. Discourse analysis of media texts is based on Dryzek’s approach to classification of environmental discourses. Three discourses are identified and investigated with respect to the means of their creation based on the analysis of the following components: tone and atmosphere, entities and their relationships, main agents, rhetoric devices. The analysis reveals how discourses create their regularities and what they might lead to when producing the climate change image. The research shows different approaches to the perception of climate change, and accordingly, towards the actions that should be taken. Beck’s world risk society is used as a theoretical anchor for addressing questions about the role of discourses in the formation of climate change meanings. It is argued that language and discourses influence social orders of society, and are capable of introducing new meanings of old concepts as well as new concepts.